The New Kenya Food Security Simulator: A Practical Demonstration and Announcement of a Blog Competition - Comstock, Andrew R. (International Food Policy Research Institute, 2023)
Andrew Comstock and Oliver Ecker use this presentation at the New Kenya Food Security Simulator: A Practical Demonstration and Announcement of a Blog Competition virtual seminar on July 19, 2023. The Kenya Food Security Simular is an innovative and easy-to-use, MS-Excel-based tool for assessing the potential short-term impacts of food price or household income shocks on food security and people’s diets.